Paris on the Neva Some of the Kirov's role models considered - Simpson, Jane (Dance Books Ltd., Alton,Hampshire (UK), 2003)
Paris on the Neva: some ot the Kirov's role models considered. PALABRAS CLAVE: Kirov, Etudes, Serenade.
Dentro del apartado "Kirov 2003".